Research Trends on Digital Literacy in Quality Education: Bibliometric Analysis Form 2000 to 2024 - Hilhamsyah; Deden Ramdani; Edeh Dike Mariske; Winarno; Suparman; Ika Mariyani (JTP - Jurnal Teknologi Pendidikan, 2025)
Digital Literacy Although many researchers discuss digital literacy, the contribution of digital literacy research to the quality of education is often fragmented, with diverse and unsystematic topics, approaches, and geographical areas. Therefore, this study aims to analyze global research patterns, trends, and focuses over time, thereby providing a foundation for more effective educational development policies and practices. The research method uses bibliometric analysis. The database used is Dimension.ai with the keywords "digital literacy" AND "quality education" in the period 2000-2024. This search results produced 19,498 publications and a total of 5,783 publications were analyzed. The results of the study show that the trend of digital literacy research in the field of quality education has increased every year. The results of this study in the field of Sustainable Development Goals (SDGs), the most publications are in the field of education with 4,159 publications. Meanwhile, the journal that published the most articles was the Journal of Education and Information Technology. The author with the most publications is Lukasz Tomczyk with 11 publications. The conclusion is that emerging themes in this field are digital literacy levels, digital literacy scales, variables, significant differences, equity, governance, and initiatives that demonstrate the research focus on measurement and policy formulation. The author group with the strongest collaboration is C.R. Safrudin Bachtiar, Abadi Moko Dwi, and Akbar Rasnoha Sunara.